Cancer mortality in 2020 and its trend analysis in Inner Mongolia during four time periods from 1973 to 2020 - Hou, Ruili; Mu, Zhiqi; Kang, Weiwei; Liu, Zhengran; Na, Buqi; Niu, Wenliang (Frontiers in Oncology, 2023)
Cancer is one of the leading causes of mortality in China and is responsible for placing a major burden on its economic system. Inner Mongolia is located close to the northern border of China, adjacent to Mongolia; it has a large east-west span and a complex and unique ethnic composition. By analysing the trend and varied causes of cancer death we are able to obtain insight that can help improve cancer prevention and control measures. We compiled data pertaining to cancer in Inner Mongolia obtained from the three national causes of death sample surveys , as well as data pertaining to cancer mortally rates from the cause of death surveillance system in Inner Mongolia in the year 2020. The proportion of deaths from various cancer, crude mortality rate and standardized rate of cancer were calculated. The Joinpoint Regression Program was used to calculate the mortality trends and the APC in these rates. We found that the mortality rate of cancer was 142.15/105; ASMRC and ASMRW were 86.49/105 and 85.73/105 in 2020. From 1971 to 2020, during the four periods , the leading five cancer types contributing to the mortality rate among Inner Mongolia residents in 2020 were stomach cancer, esophageal cancer, liver cancer , cervix/uterine cancer, and lung cancer. The four periods of time PYLL ‰ were 9.05‰,10.79‰,12.1‰, and 10.38‰ from 1971-2020.The overall trend of crude mortality rate of cancer in Inner Mongolia from 1971 to 2020 increased. Also, the crude mortality rate was higher in men than in women. The mortality rates of cancer in Inner Mongolia increased with age in the 1970s and 2020 for ages 10 to 84, and the identical trend was observed for ages between 0 and 74 in the 1990s, and the 2000s. The health and lives of Inner Mongolian citizens are gravely threatened by cancer, therefore it is important to carry out health education and raise awareness of these forms of cancer, as well as implement screening programs in accordance with the features of various malignancies, especially focusing on cancers related to the lungs, liver, stomach, and esophagus.